Customary Leadership and Ecological Preservation: Insights from the Kajang Indigenous Community, Indonesia - Yulika, Febri; Dewi, Susi Fitria; Kasman, Selvi; Fernando, Henky; Riski, Wahyu Nova; Sulaiman, Nor Lisa; Salleh, Kahirol Mohd; ., Evelynd (Journal of Ecohumanism, 2025)
Customary leadership plays a vital role in preserving ecological systems through the integration of local values and traditional wisdom. However, this phenomenon remains underexplored in existing literature. This study seeks to fill this gap by providing an in-depth analysis of the contributions of customary leaders within the Kajang Indigenous Community in South Sulawesi, Indonesia, to ecological preservation. The findings highlight three key roles of customary leadership in fostering sustainable ecological practices. First, the influence of customary leaders is pivotal in shaping community attitudes toward environmental stewardship and safeguarding natural resources. Second, the spiritual, moral, and cultural guidance provided by these leaders instills a sense of responsibility and collective action within the community, fostering sustainable ecological behavior. Third, the Kajang tribe’s values of harmony, religiosity, and adaptability are deeply embedded in their ecological preservation practices, serving as a model of sustainable living. The study underscores the importance of exploring diverse perspectives on the role of customary leadership in ecological preservation, offering valuable insights for future research and conservation efforts. These findings illuminate the potential of indigenous leadership in promoting sustainable ecological management and enriching global conservation strategies.